Farmer-to-farmer video: Grass strips against soil erosion (Lao version) - International Center for Tropical Agriculture; Agro-Insight (2015)
This farmer-to-farmer video, developed through funding by the Swiss Agency for Development and Cooperation (SDC) by CIAT and Agro-Insight, explains in a clear and simple way the agricultural technique to plant grass strips on sloping land to prevent soil erosion. The videos are prepared to deepen farmer’s understanding of the technical aspects of improved soil management, and at the same time, to prompt discussion within the local context.